Total Harmonic Distortion THDV dan THDI Per Fase Menggunakan ABB Power Meter M2M Mobus dan Fluke 435 pada Apartement Pondok Indah Residences - Deriel Apriliagung; Juhana; Sunardi (CV. Multi Kreasi Media, 2025)
The non-linear load on the power system has made the sinusoidal wave flowing in the system become very distorted which is expressed by the percentage of harmonic content, this study measured the harmonic content of current and voltage using ABB Power Meter M2M Mobus and PQA Fluke 435 measuring instruments. Furthemore, the measurent result are compared with the harmonic standards allowed based on the IEEE 519.1992 the maximum voltage distortion limit is 5% and the maximum current distortion limit is 20%. Measurement of THDI (%) and THDV (%) on each L₁, L₂, L₃. The result of this research show the state of maya tower harmonics by 2 tools namely ABB Power Meter M2M Mobus and PQA Fluke 435 starting at 10:00 – 16:00. Show the result that : 1. The shows the largest THDI and THDV on both tools are ABB Power Meter M2M Mobus THDI 18% and THDV 3%, PQA Fluke 435 THDI 19,3% and THDV 3,09%. 2. The difference in THDV measured by ABB Power Meter M2M Mobus and PQA Fluke 435 is around 0,09% while the difference in THDI measured by ABB Power Meter M2M Mobus and PQA Fluke 435 is around 1,3%. 3. THDV and THDI measured by both tools, namely ABB Power Meter M2M Mobus and PQA Fluke 435 at Pondok Indah Residences building right in the virtual LVMSB maya tower, are still included in the safe radar in the IEEE 519.1992 standard, namely THDV <5% and THDI <20%. With the condition of the electrical load at Pondok Indah Residences, it is recommended to review the LVMSB itself if necessary it would be better to install harmonic filter so that %THDI and %THDV are in a safe zone